EXTENDING THE SCOPE OF PRUDENTIAL SUPERVISION: REGULATORY DEVELOPMENTS DURING AND BEYOND THE “EFFECTIVE” PERIODS OF THE POST BCCI AND THE CAPITAL REQUIREMENTS DIRECTIVES - OJO, Marianne (Journal of Advanced Research in Law and Economics; Vol 1 No 1 (2010): JARLE Volume I Issue 1(1) Summer 2010, 2016)
The main argument of this paper is, namely, the need for greater emphasis on disclosure requirements and measures – particularly within the securities markets. This is justified on the basis of lessons which have been drawn from the recent Financial Crises, one of which is the inability of bank capital requirements on their own to address funding and liquidity problems. The engagement of market participants in the corporate reporting process, a process which would consequently enhance market discipline, constitutes a fundamental means whereby greater measures aimed at facilitating prudential supervision could be extended to the securities markets. Furthermore, the paper illustrates how through Pillar 3, market participants like credit agencies can determine levels of capital retained by banks – hence their potential to rectify or exacerbate pro cyclical effects resulting from Pillars 1 and 2. Challenges encountered by Pillars 1 and 2 in addressing credit risk are reflected by problems identified with pro cyclicality, which are attributed to banks’ extremely sensitive internal credit risk models, the level of capital buffers which should be retained under Pillar Two. Such issues justify the need to give greater prominence to Pillar 3. In elaborating on Basel II’s pro cyclical effects, gaps which exist with internal credit risk model measurements, Basel II’s risk measurements, along with the increased prominence and importance of liquidity risks - as revealed by the recent financial crisis, and proposals which have been put forward to mitigate Basel II’s procyclical effects will be addressed.
Keywords: Capital Requirements Directive (CRD), Post BCCI Directive, prudential supervision, liquidity, capital, maturity mismatches, regulation